Miscellaneous writings (gsuṅ thor bu) of Kun-mkhyen Kloṅ-chen-pa Dri-med-ʼod-zer - Kloṅ-chen-pa Dri-med-ʼod-zer, 1308-1363 (Sanje Dorje, 1973)
Writings on Lamaist theory and practice by an eminent philosopher of the Nyingmapa tradition.